Bladder stone: a rare cause of obstructed labour - Sonak, Mangala; Ramteke, Sangeeta; Davile, Medha (International Surgery Journal, 2017)
Bladder stone is a rare cause of obstructed labour. Study report a case of bladder stone obstructing the labour in a multipara. Diagnosis was made during labour on pervaginal examination. The stone was impacted below the fetal head thus obstructing labour. A bladder stone weighing approximately 120 g and measuring 6x6 cm was removed by cystolithotomy at the time of caesarean section. The postoperative period was uneventful. Mechanical cause resulting in obstructed labour is a very common phenomenon but vesical calculus causing dystocia is very rare and till date very few cases of vesical calculus resulting in obstructed labour has been reported in the literature. Prompt diagnosis of the condition is very important to prevent grave complications like vesicovaginal fistula and rupture uterus.